Focused Retrieval of Content and Structure 10th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2011, Saarbrücken, Germany, December 12-14, 2011, Revised and Selected Papers - Geva, Shlomo; Kamps, Jaap; Schenkel, Ralf (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings of the 10th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2011, held in Saarbrücken, Germany, in December 2011. The 33 revised full papers presented were carefully reviewed and selected for presentation at the workshop from 36 submissions. The papers are organized in 5 research tracks  on book and social search, Xdata centric, question answering, relevance feedback, and snippet retrieval.